Catalytic Transformation of Tall Oil into Biocomponent of Diesel Fuel - Jozef Mikulec; Andrea Kleinová; Ján Cvengroš; L'udmila Joríková; Marek Banič (International Journal of Chemical Engineering)
One of the conventional kraft pulp mills produce crude tall oil which is a mixture of free fatty acids, resin acids, sterols, terpenoid compounds, and many others. This study is devoted to the issue of direct transformation of crude tall oil in a mixture with straight-run atmospheric gas oil to liquid fuels using three different commercial hydrotreating catalysts. Diesel fuel production is an alternative to incineration of these materials. High catalytic activity was achieved for all tested catalysts in temperature range 360–380°C, under 5.5 MPa hydrogen pressure and ratio H2/feedstock 500–1000 l/l. Crude tall oil can be converted to diesel oil component via simultaneous refining with straight-run atmospheric gas oil on NiMo/Al2O3 and NiW/Al2O3-zeolite catalysts. All tested catalysts had very good hydrodenitrogenation activity and high liquid yield were at tested conditions.